Transformasi Pembelajaran Aksara Jawa Menggunakan Game Edukasi Memory Match Berbasis Android - Afit Muhammad Lukman; Fahlepi Roma Doni; Budi Sudrajat (Evolusi : Jurnal Sains dan Manajemen, 2026)
Javanese script or what is often called Hanacaraka is one of the regional cultural heritages that must be preserved. Various efforts have been made by the government, one of which is by including Javanese script material in Javanese Language Subjects starting at the elementary school level in Central Java. However, Javanese script is now starting to be reluctant to learn, considering that Javanese script is a difficult material for most students. The monotonous learning system with boring learning media is also the reason why Javanese script is starting to be reluctant to learn. By utilizing current developments in technology and information, the authors make educational games to increase student interest in learning. Games are very popular with various groups, including children. There have been many children who have and are proficient in using gadgets to play games, they even often spend time playing games that do not provide education. The role of parents is very important in this matter, but they sometimes forget to put limits on the use of gadgets for children. With this educational game, it is hoped that it will be the right choice to increase interest in learning Javanese script among students, not only at school but also at home. The data collection methods used in the making of this educational game are the observation method and the literature study method.